2010
DOI: 10.1111/j.1365-2389.2010.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterization of placic horizons in subtropical montane forest soils, northeastern Taiwan

Abstract: Well-developed placic horizons have been found in subalpine forest soils with large clay contents in Taiwan. We investigated their formation processes in five profiles in a subalpine ecosystem of northeastern Taiwan, using scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS), electron probe microanalysis (EPMA), differential X-ray diffraction (DXRD) and chemical extractions. The placic horizons, ranging from 3-to 17-mm thick, always occurred above argillic horizons with abrupt changes in pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The existence of ferrihydrite and goethite, along with some lepidocrocite, has been verified with differential XRD, SEM, EDS, micromorphology, and selective dissolution techniques (Campbell and Schwertmann, 1984;Jien et al, 2010). These data suggest that placic horizons are cemented by amorphous or weakly crystalline Fe minerals such as ferrihydrite, goethite, and lepidocrocite.…”
Section: Cementing Agents Of Ortstein and Placic Horizonsmentioning
confidence: 81%
See 2 more Smart Citations
“…The existence of ferrihydrite and goethite, along with some lepidocrocite, has been verified with differential XRD, SEM, EDS, micromorphology, and selective dissolution techniques (Campbell and Schwertmann, 1984;Jien et al, 2010). These data suggest that placic horizons are cemented by amorphous or weakly crystalline Fe minerals such as ferrihydrite, goethite, and lepidocrocite.…”
Section: Cementing Agents Of Ortstein and Placic Horizonsmentioning
confidence: 81%
“…One ofthe soils in the present study is derived from volcanic ash; three are developed from basaltic or andesitic residuum. Jien et al (2010) reported an argillic horizon below the placic horizon and suggested that clay migration leads to restricted drainage and the development of a placic horizon. In the present study six of seven pedons were underlain by either saprolite or dense till.…”
Section: Placic Horizonsmentioning
confidence: 97%
See 1 more Smart Citation
“…The high Fe o , Fe d , Al o and Al d contents in the B horizons implied that iron moved downwards and accumulated in the subsoil. Because high soil moisture and rich organic matter decreased soil redox potential in the surface layer, reduced Fe and Al ions moving from surface to the bottom layer were re-oxidized in the B horizons [49,50]. This formation of accumulated Fe, which may due to the redoximorphic process [51,52], created a placic-like horizon and resulted in slow permeability of P in such perhumid forest soil [49].…”
Section: Soil Physiochemical Properties and Chemical Extractable Pmentioning
confidence: 99%
“…The high Fe o , Fe d , Al o and Al d contents in the B horizons implied that iron moved downwards and accumulated in the subsoil. Because high soil moisture and rich organic matter decreased soil redox potential in the surface layer, reduced Fe and Al ions moving from surface to the bottom layer were re-oxidized in the B horizons [47,48]. This formation of accumulated Fe, which may due to the redoximorphic process [49,50], created a placic-like horizon and resulted in slow permeability of P in such perhumid forest soil [47].…”
Section: Soil Physiochemical Properties and Chemical Extractable Pmentioning
confidence: 99%